Pengaruh Social Media Campaign Bijakkelolasampah Terhadap Sikap Peduli Lingkungan Pada Followers Waste4change - Alessandro Dirgantara; Rizky Fauzi (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2024)
The use of single-use plastic products causes the accumulation of plastic waste. Waste4Change offers solutions for waste management through the #BijakKelola Sampah campaign. Social media campaigns allow messages to reach a very wide audience. Millions of people from various geographical locations can be reached easily through social media platforms like Instagram. Social media is quickly becoming popular as a platform that has a major influence on campaign messages. Social media and broadcasting have a complementary relationship and have an impact on how messages or content are delivered, accessed, and interacted with audiences. The aim of this research is to evaluate how the social media campaign #BijakManagewaste impacts the environmental care attitudes of @Waste4Change followers. The research method used is quantitative and uses simple linear regression analysis techniques by determining a slovin sample or 100 respondents by determining probability sampling. Distributing questionnaires to respondents via Google Form with questions with a positive Likert scale value. Processing the data that has been collected uses SPSS 26. The analysis testing techniques used include Respondent Characteristics with the criteria of Age, Gender and Education. The next tests are Descriptive Analysis, Validity Test, Reliability Test, Simple Regression Coefficient and T Test. The research results obtained are about Social Media Campaign #BijakKelolaSampah @Waste4Change on Environmental Care Attitudes It is known that the Social Media Campaign #BijakKelolaSampah @Waste4Change has a significant influence on Environmental Care Attitudes